Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How can I prove that:

$ (g^b \bmod{p})^a \bmod{p} = (g^a \bmod{p})^b \bmod{p}$

where p is a prime number, g is a primitive root of p, and a and b are integers.

While I understand that $(g^b)^a = (g^a)^b$ , I cannot figure out how to deal with the mod functions...

share|cite|improve this question

You can expand $(g^b \bmod p)$ as $g^b + pK$ by the definition of $\text{mod}$.

Then $(g^b + pK)^a = g^{ab} + \binom{a}{1}g^{(a-1)b}pK + \ldots + (pK)^a$

Since all but the first of the terms in the binomial expansion contain a factor of $p$, $(g^b \bmod p)^a \equiv g^{ab} \bmod p$

share|cite|improve this answer
How g^b mod p = g^b + pK? – codeomnitrix Jul 25 '14 at 9:42
@codeomnitrix, $a \equiv b\pmod c$ is a shorthand notation for $\exists k : a - b = ck$ – Peter Taylor Jul 30 '14 at 9:34
Thanks Peter... – codeomnitrix Jul 30 '14 at 15:35
are u sure about (g^b mod p)^a ≡ g^(ab) mod p? lets try with g = 2, a = 1, b = 3, p== 11 (2^3 mod 11) ^ 5 != 2 ^ (5*3) mod 11 as obviously 8^5 != 2^15 mod 11 – Dmitry Martovoi Jun 30 at 11:27
@DmitryMartovoi, I have no idea where your 5 came from, but yes, I am sure because I am completely convinced by the proof in the answer. I am also completely convinced that "8^5 != 2^15 mod 11" is obviously false: $8^5 = 2^{15}$ so there's no need to even compute the values mod 11. – Peter Taylor Jun 30 at 11:33

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.